Patient Characteristics, Locations and Histopathological Features of Steatocystoma Multiplex Cases - Balta, Hilal; Çalık, İlknur; Durmuş, Şenay Erdoğan; Özmen, Sevilay; Bilici, Ahmet Erkan (Karyay Karadeniz Yayımcılık Ve Organizasyon Ticaret Limited Şirketi, 2022)
Steatocystoma multiplex (SM) is a rare benign genetic disorder consisted of multiple cystic with little or no nail and hair involvement. Steatocystoma is a hamartomatous malformation of the pilosebaceous unit consisting of dermal cysts filled with a sebum-like material. To examine the patient characteristics, locations, presentations and histopathological features of SM in a group of patients. We analyzed 9 patients retrospectively that histopathologically diagnosed as SM. Demographic data collected from pathology reports. Patients’ mean age was 43.7 years (range: 15-69 years), with a male to female ratio of 7:2. The average diameter of the lesion at presentation was 13.2 mm (range: 2–30 mm), although 4 cases were less than or equal to 5 mm in size. The lesions located in neck, conjuctiva, face and frontal region. The most common clinical presentation was a painless skin lesion which was noticed incidentally. Histopathological examination of skin showed presence of cystic formation with sebaceous gland on its wall in the dermis and typical stratified squamous epithelium that showed wavy shaped stratum corneum, refractile and strong eosinophilic infiltrated in the cystic wall. SMs are benign lesions more frequent in male patients and especially located in head and neck region. These lesions may be misdiagnosed or underreported.
Keywords: Clinical Sciences; Klinik Tıp Bilimleri